2013
DOI: 10.1162/rest_a_00274
|View full text |Cite
|
Sign up to set email alerts
|

Do Countries Falsify Economic Data Strategically? Some Evidence That They Might

Abstract: Using Benford's law, we find evidence supporting the hypothesis that countries at times misreport their economic data strategically. We group countries with similar economic conditions and find that for countries with fixed exchange rate regimes, high negative net foreign asset positions, negative current account balances, or more vulnerable to capital flow reversals, we reject the first-digit law for the balance-of-payments data. This corroborates the intuition of a simple economic model. The main results do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 29 publications
(36 reference statements)
0
68
0
Order By: Relevance
“…The idea that Benford's Law could be used to detect errors in economic data was first suggested by Varian (1972) with relation to economic forecasts. More recently, Michalski and Stoltz (2013) showed that this method can be used to detect errors in macroeconomic data. Carslaw (1988) used a variant of Benford's Law to argue that firms in New Zealand whose earnings did not conform to the law were rounding up their earnings numbers.…”
Section: Motivation and Contributionmentioning
confidence: 99%
“…The idea that Benford's Law could be used to detect errors in economic data was first suggested by Varian (1972) with relation to economic forecasts. More recently, Michalski and Stoltz (2013) showed that this method can be used to detect errors in macroeconomic data. Carslaw (1988) used a variant of Benford's Law to argue that firms in New Zealand whose earnings did not conform to the law were rounding up their earnings numbers.…”
Section: Motivation and Contributionmentioning
confidence: 99%
“…35. Michalski and Stoltz (2013) find evidence that countries may strategically misreport their economic data. output, results from other studies that rely on other macroeconomic data could be more fragile than those in our sample.…”
Section: Discussionmentioning
confidence: 97%
“…Michalski and Stoltz () find evidence that countries may strategically misreport their economic data.…”
mentioning
confidence: 99%
“…For more on the history of the normal distribution, see the work of Patel and Read (1982). 3 Creative applications of Benford's Law are found in connection with religious data (Makous, 2011;Mir, 2012), election frauds (Leemann & Bochsler, 2014), population studies (Sandron, 2002), auctions on eBay (Giles, 2007), survey data (Judge & Schechter, 2009), tax data (Nigrini, 1996), economic data (EU) (Michalski & Stoltz, 2013), Libor manipulations (Abrantes-Metz et al, 2012), accounting fraud detection (Nigrini, 1999), and financial reporting (McGuire, Omer, & Sharp, 2011). For a detailed list of useful application of Benford's Law, see Hürlimann (2006).…”
Section: Endnotesmentioning
confidence: 99%